1981
DOI: 10.1111/j.1365-2648.1981.tb03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Polygamy: a cultural trait and maternal and child health

Abstract: This study indicates that it is probable that the cultural trait of polygamy was instituted as an adaptive measure in a particular ecology within a particular tribal group. Polygamy perpetuated because of its positive contribution to maternal and child health. The study further indicates that it is also probable that monogamy as a foreign cultural trait and its introduction without concomitant changes in other spheres of the ecosystem (biophysical and social environment) must have produced a negative effort on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, polygynous families differ in important functional aspects from nuclear households in that often there is cooperation between cowives, and extended family networks are commonly important sources of child care and labor (Shell-Duncan, 1994;Whyte and Kariuki, 1991). Some studies in African societies have found that children living in polygynous households are less likely to be malnourished than those in monogamous households (George, 1981), whereas others have found no such effect (Burgess et al, 1972;Desai, 1991;Vella et al, 1992;Sellen, 2000). The lack of consistent findings suggests that the effect of household type may vary under differing socioeconomic conditions.…”
Section: Family Typementioning
confidence: 99%
“…However, polygynous families differ in important functional aspects from nuclear households in that often there is cooperation between cowives, and extended family networks are commonly important sources of child care and labor (Shell-Duncan, 1994;Whyte and Kariuki, 1991). Some studies in African societies have found that children living in polygynous households are less likely to be malnourished than those in monogamous households (George, 1981), whereas others have found no such effect (Burgess et al, 1972;Desai, 1991;Vella et al, 1992;Sellen, 2000). The lack of consistent findings suggests that the effect of household type may vary under differing socioeconomic conditions.…”
Section: Family Typementioning
confidence: 99%